Evaluación de las tres especies de Granos Andinos (Chocho, Quinua y Amaranto), con el Polímero Newgel, Hidratado y sin hidratar, en Pilonera Salache. Latacunga. Cotopaxi 2017. - Tomalo Guanoluisa, Luis Rolando (2017)
This project was done in Salache neighbor, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province located at a height of 2725 meters, Latitude 00 ° 59 "47.68" S and Longitude 78 ° 37 "19.16" E. The research methods were hydrated and no hydrated polymers applied to three species of Andean grains (chocho, quinoa, amaranth), the number of plots was 27, which were distributed in 9 treatments with 3 replicates. A completely random block design was applied. The efficiency of the treatments was measured based on the index of germination in pilonera and the adaptability in the field during one month. The hydrated polymer was the most efficient method for the height of the plant at 32 days, obtaining greater results in the pilonera due to its capacity of retention of water. The non-hydrated polymer resulted in the second method with germination indexes in pilonera and field adaptability during one month. By means of the obtained results it is revealed that the hydrated and no hydrated polymers fulfill very receptive functions and important in agriculture. The percentage of germination in the three species of Andean grains presented a percentage greater than 90% in the handling of the pilonera, knowing that each germination dish had two polymers. At the height of the plant there was also no influence of the polymer, because each of the species of Andean grains presented averages according to each phenological stage in which they were between 8 and 32 days. For the variable appearance of true leaves, it is concluded the average days for each species of Andean grain was 14 days for quinoa, 12 for amaranth and 10 days for chocho. The stalk diameter at 8 days and at 32 days presented for chocho, as the species with the highest average with 2.1 and 3.03 respectively. At root length in chocho was obtained the best averages at 8 days and 32 days of the other species of Andean grains with 6.52 and 10.74 cm, respectively. There were no significant differences for any species of Andean grain in the field after transplant, indicating that there was no mortality of seedlings. For the height of the plants after the transplant, it was observed that the chocho presented the best average with 27.9 cm at 32 days, while the quinoa and amaranta obtained close averages with 17.2 and 16.29 cm respectively. For the stem diameter after the transplant, it is observed that the best average was for amaranth with 6.8 mm and the polymer hydrated with 6.67 mm.